Hippocampal Volumes in Amnestic and Non-Amnestic Mild Cognitive Impairment Types Using Two Common Methods of MCI Classification. (16th April 2022) - Emmert, Natalie A.; Reiter, Katherine E.; Butts, Alissa; Janecek, Julie K; Agarwal, Mohit; Franczak, Malgorzata; Reuss, James; Klein, Andrew; Wang, Yang; Umfleet, Laura Glass
Abstract: Objectives: Mild cognitive impairment (MCI) types may have distinct neuropathological substrates with hippocampal atrophy particularly common in amnestic MCI (aMCI). However, depending on the MCI classification criteria applied to the sample (e.g., number of abnormal test scores considered or thresholds for impairment), volumetric findings between MCI types may change. Additionally, despite increased clinical use, no prior research has examined volumetric differences in MCI types using the automated volumetric software, Neuroreader™. Methods: The present study separately applied the Petersen/Winblad and Jak/Bondi MCI criteria to a clinical sample of older adults ( N = 82) who underwent neuropsychological testing and brain MRI. Volumetric data were analyzed using Neuroreader™ and hippocampal volumes were compared between aMCI and non-amnestic MCI (naMCI). Results: T-tests revealed that regardless of MCI classification criteria, hippocampal volume z -scores were significantly lower in aMCI compared to naMCI ( p 's < .05), and hippocampal volume z -scores significantly differed from 0 (Neuroreader™ normative mean) in the aMCI group only ( p 's < .05). Additionally, significant, positive correlations were found between measures of delayed recall and hippocampal z -scores in aMCI using either MCI classification criteria ( p' s < .05). Conclusions: We provide evidence of correlated neuroanatomical changes associated with memory performance for two commonly used neuropsychological MCI classification criteria. Future research should investigate the clinical utility of hippocampal volumes analyzed via Neuroreader™ in MCI.